Pelatihan Penulisan Artikel Ilmiah Bagi Guru-guru Sekecamatan Taman Madiun - Hadi, Fida Rahmantika; Suyanti, Suyanti; Novan Ramadhan, Wemphi; Setiawati, Wiwik (Jurnal Pengabdian Kepada Masyarakat, 2022)
The demand for competence for teachers today is not an easy task or thing. In general, teachers do not understand about writing scientific articles that are worthy of publication. Even though this is one of the supports in developing self-competence that must be owned by teachers. The purpose of this service is to provide training for teachers in writing scientific articles. The partners of this service are teachers from the Madiun district. The methods used in this training activity are lectures, discussions, questions and answers, guidance and consultation. The implementation of this service goes through three stages, namely preparation, implementation and evaluation. This training activity is a form of fostering the ability of teachers to write scientific articles. It is hoped that after participating in this training activity, activity participants can write scientific articles that are worthy of publication